2009 IEEE Power &Amp; Energy Society General Meeting 2009
DOI: 10.1109/pes.2009.5275492
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the North American interconnections at distribution level

Abstract: The North American Frequency Monitoring Network (FNET) is a wide-area measurement system that monitors the North American Interconnections at distribution voltage level. A situational awareness system has been implemented on the server located at Virginia Tech to detect and analyze power system disturbances in near-real time. This paper demonstrates the viability of monitoring bulk transmission systems at a very low voltage level by discussing several major disturbances in the Eastern Interconnection (EI) obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To acquire this data for research purposes may take many months and access may be limited. However, it has been shown that transmission side disturbances can be detected at the distribution level [5], [6]. These disturbances on the transmission system are reflected in system variables (frequency, voltage magnitude, and phase angle) that are measured by PMUs at the distribution side [6].…”
Section: B Distribution Side Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…To acquire this data for research purposes may take many months and access may be limited. However, it has been shown that transmission side disturbances can be detected at the distribution level [5], [6]. These disturbances on the transmission system are reflected in system variables (frequency, voltage magnitude, and phase angle) that are measured by PMUs at the distribution side [6].…”
Section: B Distribution Side Measurementsmentioning
confidence: 99%
“…However, it has been shown that transmission side disturbances can be detected at the distribution level [5], [6]. These disturbances on the transmission system are reflected in system variables (frequency, voltage magnitude, and phase angle) that are measured by PMUs at the distribution side [6]. It has been observed that disturbances occurring on the transmission side are also seen in the distribution side measurements taken by PMUs in the Texas synchrophasor network [1].…”
Section: B Distribution Side Measurementsmentioning
confidence: 99%
See 1 more Smart Citation